Tax Extensification: A Review of the Bengkulu City Government's Strategy to Increase Local Revenue - Hadinata, Ruddy Tri Hendra; Yogopriyatno, Jatmiko (KnE Social Sciences, 2025)
This research study focuses on developing strategies to increase local revenue by utilizing strategic management theory and Strength Weakness Opportunities Threats (SWOT) analysis framework. The researchers adopted a descriptive quantitative analysis method to examine the issues at hand and provide explanations. The study involved a sample of 30 respondents, and the analysis involved weighting to determine the Internal Factor Analysis Strategy (IFAS) and External Factor Analysis Strategy (EFAS) values. These values were then entered into the SWOT Quadrant for further analysis. Qualitative data analysis revealed various internal (Strength-Weakness) and external (Opportunities-Threats) factors. The results showed that the IFAS value was 1.91 and the EFAS value was 1.89, both of which were in Quadrant I. Further analysis using the Quantitative Strategic Planning Matrix (QSPM) identifies the strategies that have been obtained and then determines the strategies that should be prioritized from the 9 strategies as follows, Increase of facilities and infrastructure in managing Local Owned Revenue (LOR), Provide functional training on local taxes and levies, Improving regional revenue management by optimizing potential in the form of LOR potential studies. and others.